2022
DOI: 10.1080/21645515.2022.2102329
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 vaccination perception and uptake among cancer patients in Guangzhou, China

Abstract: Patients with cancer are considered at high risk of COVID-19 related complications with higher mortality rates than healthy individuals. This study investigated the perception, acceptance, and influencing factors of COVID-19 vaccination among cancer patients in Guangzhou, China. A cross-sectional survey was conducted in Guangzhou, China from August to November 2021 in two tertiary medical centers. Outpatients were recruited through hospital posters to complete a questionnaire including demographics, medical hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 33 publications
1
4
0
Order By: Relevance
“…These results suggest older age is a predictive factor for adequate vaccination against COVID-19 among patients with cancer. Furthermore, positive attitudes towards COVID-19 vaccines have also been associated with higher acceptance of COVID-19 vaccination in patients with cancer in other studies [26,[28][29][30][34][35][36][37]. In our survey, positive attitudes, such as believing that COVID-19 vaccines are safe in patients with cancer also increased the likelihood of having an adequate vaccination status (≥ 3 doses).…”
Section: Discussionsupporting
confidence: 69%
“…These results suggest older age is a predictive factor for adequate vaccination against COVID-19 among patients with cancer. Furthermore, positive attitudes towards COVID-19 vaccines have also been associated with higher acceptance of COVID-19 vaccination in patients with cancer in other studies [26,[28][29][30][34][35][36][37]. In our survey, positive attitudes, such as believing that COVID-19 vaccines are safe in patients with cancer also increased the likelihood of having an adequate vaccination status (≥ 3 doses).…”
Section: Discussionsupporting
confidence: 69%
“…Vaccines of COVID‐19 have been proven to be safe and effective for preventing infection or attenuating disease severity and are also recommended to cancer patients. However, the concerns of vaccines included cancer progression, potential long‐term toxicity, or interfere with treatment resulted in a low acceptance of the vaccine in cancer patients in China 29–31 . In our study, only 34.5% of patients were vaccinated against COVID‐19 and 10% of patients had received the third dose of vaccines.…”
Section: Discussionmentioning
confidence: 68%
“…However, the concerns of vaccines included cancer progression, potential long-term toxicity, or interfere with treatment resulted in a low acceptance of the vaccine in cancer patients in China. [29][30][31] In our study, only 34.5% of patients were vaccinated against COVID-19 and 10% of patients had received the third dose of vaccines. The lower vaccine serologic response was reported in HM patients, particularly those with lymphoid cancers and/or receiving anti-CD20 therapy with impaired immune function [32][33][34][35] ; thus, the protective effect of vaccine might be limited in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…The second sensitivity analysis was the exclusion of Fu et al [23] from the meta-analysis for income. This was done in order to assess whether this study was a detrimental outlier and played a significant role in the overall uptake outcome.…”
Section: Sensitivity Analysismentioning
confidence: 99%
“…Furthermore, this systematic review found that the lowest acceptance rate of COVID-19 vaccination was amongst patients with chronic diseases (42.6%). These patients were diagnosed with diseases such as asthma, HIV/AIDS, cancer, and hypertension [39,27,23,19,20].…”
Section: Vaccine Hesitancy Among Those With Underlying Health Conditionsmentioning
confidence: 99%